Созологічний аналіз дендроекзотів дендропарку “Олександрія” НАН України - Kalashnikova, L.V.; Galkin, S.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
Results of the study quantitative and quantitative composition of species, sozological status, geographical origin and vitality of rare fraction of woody plants in Dendrological park Olexandria of the NAS of Ukraine are given. Based on the 2016 inventory studies, it was found that rare faction includes 105 species that are divided into 2 divisions, 3 classes, 32 families, 59 genera, including representatives of Pynophyta 19 species (18 %), that belong to 5 families and the rest is representatives of Magnoliophyta, that belong to 27 families. By the soziological status, in IUCN Red List include 52 species, in European Red List – 37 species, 12 (11 %) species that are protected by both Red List. 28 (27 %) species are protected by the Red Book of Ukraine, including 6 endangered, 11 vulnerable, 10 rare species, and 1 is not valuated. The list of regionally rare species for Kyiv Region includes 7 species. Age-old trees include 18 (17 %) species, and most of them are the oldest exotic species in Ukraine. The most species originate from Europe (47 species, 44.8 %), North America and Eurasian (24 species, 22.0 %). The results of outphytosozological assessment of dendroexotics of park are classified as II–V outphytosozological classes. The II class (the most rare species of trees and shrubs) includes 6 (5.7 %) species, the III class – 37 (35.0 %), the IV class – 41 (39.0 %), the V class – 9 (8.6 %). The characteristics of vitality of dendrosozophytes in terms of "life form", "the capacity for generative and vegetative development", "winter-hardiness", "drought tolerance", "the degree of resistance to abiotic factors" are given.